Robert H. Rubin and infectious disease in transplantation - Fishman, Jay A. (Frontiers in Transplantation, 2023)
Robert H. Rubin, M.D. was among the first physician-scientists to focus attention on the infectious diseases associated with immune suppression. A superb bedside clinician and teacher, he developed many of the concepts central to the care and improved survival of organ transplant and stem cell transplant recipients. These concepts have provided the basis of clinical investigation and basic research for multiple generations of infectious disease specialists, immunologists, and transplant surgeons.